A high-resolution natural abundance 33S MAS NMR study of the cementitious mineral ettringite. Issue 35 (24th August 2017) - Sasaki, Akiko; Ibarra, Luis Baquerizo; Wimperis, Stephen
Abstract : Natural abundance 33 S STMAS NMR spectroscopy is used to determine the 33 S chemical shift and quadrupolar parameters in the cement-forming mineral ettringite. Abstract : Despite the widespread occurrence of sulfur in both natural and man-made materials, the 33 S nucleus has only rarely been utilised in solid-state NMR spectroscopy on account of its very low natural abundance (0.76%), low NMR frequency ( ν 0 = 30.7 MHz at B 0 = 9.4 T), and significant nuclear quadrupole moment (spin I = 3/2, Q = −69.4 mb). Satellite-transition magic angle spinning (STMAS) is an NMR method for obtaining high-resolution spectra of half-integer quadrupolar nuclei (spin I > 1/2) in solids and is notable for its intrinsic sensitivity advantage over the similar multiple-quantum (MQMAS) method, especially for nuclei with low NMR frequencies. In this work we demonstrate the feasibility of natural abundance 33 S STMAS NMR experiments at B 0 = 9.4 T and 20.0 T using a model sulfate sample (Na2 SO4 + K2 SO4 in a 1 : 1 molar ratio). Furthermore, we undertake a natural abundance 33 S STMAS NMR study of the cement-forming mineral ettringite (Ca6 Al2 (SO4 )3 (OH)12 ·26H2 O) at B 0 = 9.4 T and 20.0 T, resolving a discrepancy in the literature between two previous conventional 33 S MAS NMR studies and obtaining an alternative set of 33 S NMR parameters that is simultaneously consistent with the MAS and STMAS data at both field strengths.